Influence of Parks and Urban Forest on the Prices of Residential Real Estate in Skopje - Penchikj, D. and Dichova, Vesna G. (Faculty of Civil Engineering -Skopje, University Ss. Cyril and Methodius Skopje, 2021)
The main purpose of this research was to examine the aspects of urban planning that affect the determining of real estate values and their changes, when planning the spatial development of cities and settlements. The basis for the conducted research was review and analysis of the role of urban planning and urban plans, and the significance of real estate and real estate values. Crucial for the case study were the results obtained from examining the relation between urban planning and the value of real estate and determining the aspects that influence urban planning as a factor in determining the value of real estate. The research was conducted for the city of Skopje, as a capital and also a city based on which the urban policy of the entire country is created. The conducted case studies have been selected based on specific aspects of the urban conditions that directly affect the change of the real estate value.
Keywords: urban planning, urban plans, real estate, value of real estate